1979
DOI: 10.1136/adc.54.12.954
|View full text |Cite
|
Sign up to set email alerts
|

Lymphocyte changes in beta-thalassaemia major.

Abstract: SUMMARY Lymphocyte subpopulations were studied in 20 hypertransfused patients with ,B-thalassaemia major, some of whom had been splenectomised. B-lymphocytes were normal but T-lymphocytes were decreased in all patients. The T-cell count was lower in the splenectomised patients than in the nonsplenectomised ones. In the former, the active rosette-forming lymphocytes were also diminished, but the difference was not significant. In all patients the percentage of null cells was greater and the activity of K-cells … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
9
0

Year Published

1980
1980
1997
1997

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 9 publications
4
9
0
Order By: Relevance
“…deficient suppressor activity, must also be considered. A reduction of peripher al E-rosetting cells has recently been report ed in these patients [9], We also observed this in some of our not yet transfused pa tients, even after incubation with thymic hormone (TP-1 Serono®, Rome, Italy). However, the increased humoral response to exogenous antigen, but not to host anti gen, is not in accordance with this hypothe sis.…”
Section: Discussionsupporting
confidence: 57%
“…deficient suppressor activity, must also be considered. A reduction of peripher al E-rosetting cells has recently been report ed in these patients [9], We also observed this in some of our not yet transfused pa tients, even after incubation with thymic hormone (TP-1 Serono®, Rome, Italy). However, the increased humoral response to exogenous antigen, but not to host anti gen, is not in accordance with this hypothe sis.…”
Section: Discussionsupporting
confidence: 57%
“…In our study, all thalassemia patients showed lower NK cytotoxic activity in comparison to healthy subjects, prob ably as a consequence of multiple blood transfusions and/ or repeated viral infections, confirming the immunodefi ciency of thalassemia patients [31]. Moreover, the re duced NK activity before a-IFN treatment in thalassemia patients could be due to a poor production of a-IFN, which is essential for natural cytotoxicity.…”
Section: Resultsmentioning
confidence: 52%
“…In the present study we assessed NK ac tivity and T lymphocyte subpopulations in homozygous beta thalassemia, a severe transfusion-dependent anemia, in which some studies of cell-mediated immunity have been so far reported [4,13,19,21]. Patients with hemoglobinopathies suffer rather frequently from bacterial and viral infections; furthermore, the incidence of malignancies in thalassemia major (TM) may be an issue of interest, since hyper transfusion regimens together with inten sive removal of iron excess have signifi cantly improved the outcome of the dis ease, and at present the life expectancy of these subjects is lengthened [ 16],…”
Section: Introductionmentioning
confidence: 99%